PENGARUH INTRUKSI BERSAMA (INBER) TERHADAP KINERJA PEGAWAI KANTOR SISTEM ADMINISTRASI MANUNGGAL SATU ATAP (SAMSAT) KABUPATEN SUMBAWA - Putri Karmita; Maya Insani; Wahyu Haryadi (Pusat Riset dan Publikasi, 2022)
The SAMSAT office as a public organization is required to improve its performance well in order to serve the community as taxpayers as best as possible and to satisfy taxpayers, but in reality the performance of SAMSAT employees is not optimal so that SAMSAT services have not been able to satisfy taxpayers, starting from the existence of levies that are not Officially, the length of service time to the lack of service support facilities, especially the number of vehicles in Sumbawa Regency is very large and the increase in the number of vehicles from year to year is quite rapid. The purpose of this study was to determine the effect of Joint Instruction (INBER) on improving the performance of SAMSAT employees in Sumbawa Regency. The type of research that will be conducted is associative research. The variables in this study are the INBER variable and the performance variable which is measured using a Likert scale. The research population in this study were 33 SAMSAT employees. The analytical tools used are simple linear regression. Based on the data analysis that has been carried out, the results show that the application of joint intrusion (INBER) has a positive and significant effect on the performance of SAMSAT employees in Sumbawa Regency. The effect of implementing Joint Intrusion (INBER) on the performance of SAMSAT employees in Sumbawa Regency is 61.1%, while the remaining 38.9% is influenced by other variables not examined.